Pedestrian Priorities: Unraveling Walkability Challenges in Shah Alam's Neighborhoods - Rashid, Quraishia; Zhang, Andi; Mohd Nor, Marina (Institute of Research and Community Services of Universitas Tanjungpura and Center of Southeast Asian Ethnicities, Cultures and Societies (Joint collaboration between Universitas Tanjungpura and National Taitung University), 2024)
This article explores the contemporary shift in urban studies towards prioritizing walkable neighborhoods amidst growing concerns about urban sprawl and its environmental impacts. Focusing on Persiaran Bestari in Shah Alam, Malaysia, the research aims to address the lack of pedestrian-friendly infrastructure and the consequent reliance on vehicular transport in residential areas. This research utilizes a mixed-method approach incorporating quantitative and qualitative methodologies, combining space syntax analysis and behavioral mapping to examine pedestrian movement within the study area. The data collection involves gathering pedestrian infrastructure data through field surveys and pedestrian volume surveys. As the result, behavioral mapping observations revealed varying pedestrian activity levels along different road corridors, with significant pedestrian traffic concentrated around residential zones. Utilizing space syntax analysis, the research detected that Persiaran Bestari and Permai experienced the highest levels of social and commercial activity, indicating higher resident density in these areas. This research highlights the correlation between pedestrian comfort and safety and the availability of pedestrian infrastructure. It reveals that inadequate infrastructure leads to poor walkability, prompting pedestrians to favor safer routes, such as neighborhood or local roads with reduced and slower vehicle traffic.